2009
DOI: 10.1086/597620
|View full text |Cite
|
Sign up to set email alerts
|

Cytokine Polymorphisms and Severity of Tubal Damage in Women withChlamydia‐Associated Infertility

Abstract: Chronic inflammation induced by Chlamydia trachomatis can lead to tubal factor infertility (TFI). To investigate the genetic basis of chlamydial TFI and various manifestations of tubal damage, we studied functional polymorphisms in selected cytokine genes (IL-10 -1082 A/G, -819 T/C, and -592 A/C; IFN-gamma +874 T/A; TNF-alpha -308 G/A; TGF-beta1 codons 10 T/C and 25 G/C; and IL-6 -174 G/C) in 114 women with laparoscopically verified TFI (hereafter known as "cases") and in 176 controls. Evidence of past infecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
53
1
7

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(64 citation statements)
references
References 37 publications
(39 reference statements)
3
53
1
7
Order By: Relevance
“…The role of TNF-␣ in chlamydial pathogenesis seems to be more certain. First, TNF-␣ polymorphism has been linked to increased risk of severe tubal damage in women with infertility associated with C. trachomatis (32). Second, mice genetically deficient in TNF-␣ production displayed significantly reduced hydrosalpinx (33).…”
mentioning
confidence: 99%
“…The role of TNF-␣ in chlamydial pathogenesis seems to be more certain. First, TNF-␣ polymorphism has been linked to increased risk of severe tubal damage in women with infertility associated with C. trachomatis (32). Second, mice genetically deficient in TNF-␣ production displayed significantly reduced hydrosalpinx (33).…”
mentioning
confidence: 99%
“…Several cytokines have been studied in women who developed tubal pathology. Some associations were found: IL10 -1082 A allele together with HLA -DQA1*0102 and HLA -DQB1*0602 alleles; these were associated with severe tubal pathology [30,32]. Both the TNF-α -308 A allele and the IL6 CC genotypes were found to be associated with tubal pathology: the former as a risk factor and the latter as a protective factor for tubal pathology [32].…”
Section: Cytokinesmentioning
confidence: 99%
“…A statistically significant association between the IFNg +874 polymorphism and chlamydial tubal pathology was not found [32], nor for IL1B +3954, IL1B -511, and IL1RN gene polymorphisms [33]. However, a study performed in an ex vivo model showed that IL1, in the absence of its antagonist IL1RA, causes destruction of the ciliated cells in the Fallopian tubes [34].…”
Section: Cytokinesmentioning
confidence: 99%
“…In a retrospective study of 84 infertile women with tubal occlusion, the sera collected from 28% of these women were positive for chlamydial anti-IgG antibody, compared to only 11% positivity to the chlamydial anti-IgG antibody in sera collected from 253 infertile controls (Merki-Feld et al, 2007). A study of 114 women with laparoscopically-verified tubal factor infertility (of which 96 cases showed evidence of past infection with Chlamydia) was undertaken to further elucidate the mechanisms of tubal damage in women with Chlamydia-associated infertility (Ohman et al, 2009). The functional polymorphisms in selected cytokine genes [including IL-10, interferon gamma (IFN-), tumour necrosis factor alpha (TNF-] revealed an increase in severe tubal damage in women with infertility caused by Chlamydia when certain IL-10 and TNF-alleles were present (Ohman et al, 2009).…”
Section: Chlamydia Tubal Pathology and Tubal Factor Infertilitymentioning
confidence: 99%
“…A study of 114 women with laparoscopically-verified tubal factor infertility (of which 96 cases showed evidence of past infection with Chlamydia) was undertaken to further elucidate the mechanisms of tubal damage in women with Chlamydia-associated infertility (Ohman et al, 2009). The functional polymorphisms in selected cytokine genes [including IL-10, interferon gamma (IFN-), tumour necrosis factor alpha (TNF-] revealed an increase in severe tubal damage in women with infertility caused by Chlamydia when certain IL-10 and TNF-alleles were present (Ohman et al, 2009). In terms of cytokine secretions in Chlamydia-positive infertile women, it has been reported that Chlamydia-stimulated cervical cells secreted significantly higher levels of IL-1ß, IL-6, IL-8 and IL-10.…”
Section: Chlamydia Tubal Pathology and Tubal Factor Infertilitymentioning
confidence: 99%